PENERAPAN PSAK NO. 18 TENTANG AKUNTANSI DAN PELAPORAN PROGRAM MANFAAT PURNAKARYA PADA UNIVERSITAS SURABAYA - Agung Sri Wardhani; Bambang Herwanto (Jurnal Bisnis Terapan, 2017)
Pension scheme is the employees’ income management program that can be set aside during the employment period and it is invested so when the employees are retired, they receive the pension money regularly during their lifetime. The managers of pension fund in presenting the financial statements must refer to the prevailing rules. Guidelines of organizing financial statements for pension fund has been set in Undang Undang No. 11. Tahun 1992. Besides that, it has to be consistent with PSAK (Pernyataan Standar Akuntansi Keuangan – Standard Statement of Financial Accountancy ) No. 18. The purpose of this research is to find out and analyze the application of PSAK no. 18 on the management of pension fund in Universitas Surabaya (UBAYA). The research method used is qualitative descriptive. The result of the research showed that overall UBAYA’s management of pension fund is already matched with PSAK no. 18.